Taxonomy of Dicopus psyche Girault, 1912 (Hymenoptera: Mymaridae) and its association with Psocathropos lachlani Ribaga, 1899 (Psocodea: Psyllipsocidae) in houses in Taiwan. (3rd April 2022) - Triapitsyn, Serguei V.; Chan, Mei-Ling
ABSTRACT: The cave barklouse Psocathropos lachlani Ribaga, 1899 (Psocodea: Psyllipsocidae) occurs in many tropical and subtropical areas of the world, where it is a frequent dweller inside buildings. Numerous specimens of an egg parasitoid Dicopus psyche Girault, 1912 (Hymenoptera: Mymaridae) were collected by yellow pan traps and commercial cockroach sticky traps inside houses infested with P. lachlani in two urban localities in Taiwan. This apparent association with P. lachlani is the third known host record for the genus Dicopus Enock, 1909, which is newly recorded from Taiwan. Taxonomic notes and digital images are provided for the holotype male of D. psyche from Fiji as well as for its both sexes based on specimens from Taiwan. Dicopus longipes (Subba Rao, 1984), syn. nov ., originally described as Kubja longipes Subba Rao and known from Cambodia, India and Malaysia, is synonymised with D. psyche .